Clinical application of three-dimensional printed models in preoperative planning of pancoast tumour resection - Yek, Wen Yi; Wong, Y.H.; Yeong, C.H.; Sun, Zhonghua (The Australasian Medical Journal pty ltd., 2020)
Background